2018
DOI: 10.5483/bmbrep.2018.51.4.185
|View full text |Cite
|
Sign up to set email alerts
|

Force-mediated proinvasive matrix remodeling driven by tumor-associated mesenchymal stem-like cells in glioblastoma

Abstract: In carcinoma, cancer-associated fibroblasts participate in force-mediated extracellular matrix (ECM) remodeling, consequently leading to invasion of cancer cells. Likewise, the ECM remodeling actively occurs in glioblastoma (GBM) and the consequent microenvironmental stiffness is strongly linked to migration behavior of GBM cells. However, in GBM the stromal cells responsible for force-mediated ECM remodeling remain unidentified. We show that tumor-associated mesenchymal stem-like cells (tMSLCs) provide a proi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The concept of tumor cell traps, which emerged from the ecological trap strategy, was developed for brain tumors as a means of attracting the residual cancer cells surrounding the surgical cavity to the cavity, where they are trapped within a biomaterial support that can be targeted by treatment, such as stereotactic radiosurgery [ 46 , 47 ]. As indicated above, we and others have shown that GASCs increase the invasiveness of GB cells [ 10 , 12 , 13 , 17 , 24 , 25 ]. Based on this knowledge, we used GASC-conditioned medium as a source of chemoattractants to load the trap.…”
Section: Gascs: a Future Treatment Target Or Therapeutic Tool?mentioning
confidence: 80%
See 3 more Smart Citations
“…The concept of tumor cell traps, which emerged from the ecological trap strategy, was developed for brain tumors as a means of attracting the residual cancer cells surrounding the surgical cavity to the cavity, where they are trapped within a biomaterial support that can be targeted by treatment, such as stereotactic radiosurgery [ 46 , 47 ]. As indicated above, we and others have shown that GASCs increase the invasiveness of GB cells [ 10 , 12 , 13 , 17 , 24 , 25 ]. Based on this knowledge, we used GASC-conditioned medium as a source of chemoattractants to load the trap.…”
Section: Gascs: a Future Treatment Target Or Therapeutic Tool?mentioning
confidence: 80%
“…GASCs have been isolated from primary cultures of cells from mouse orthotopic transplantation tumor models [ 7 , 8 ], human low-grade gliomas (LGGs), human high-grade gliomas (HGGs) [ 2 , 3 , 4 , 5 , 6 , 8 , 9 , 10 , 11 , 12 , 13 , 15 , 18 , 19 , 20 , 26 ], and the peritumoral region of glioblastomas (GBs) [ 22 , 23 , 24 , 25 ] ( Table 1 ). Cultured GASCs are spindle-shaped, adherent in culture, can be subcultured many times, and express the mesenchymal surface markers CD73, CD90, and CD105.…”
Section: General Characteristics Of Gascsmentioning
confidence: 99%
See 2 more Smart Citations
“…GA‐MSC modifications of GBM microenvironment are also dependent on CCL2 release, which mediates the activation of JAK1 to regulate actin‐myosin contractility and TME and tissue mechanical stiffness needed to promote the motility of tumor cells. Therefore, GA‐MSC contribute to ECM remodeling modifying GBM stiffness similarly to what CAFs do in carcinomas 107 . Recently, the same authors reported that C5a released by GA‐MSCs increases ZEB1 levels in GBM cells through the activation of C5aR1 and p38 MAPK signaling, promoting the invasiveness of GBM without modifying growth rate in vitro.…”
Section: Crosstalk Between Msc and Gbm Cells: Direct And Indirect Intmentioning
confidence: 87%